Keep watching the skies! : the story of Operation Moonwatch & the dawn of the space age - McCray, Patrick (W. Patrick) (Princeton University Press, 2008)
"When the Soviets launched Sputnik in 1957, thousands of ordinary people across the globe seized the opportunity to participate in the start of the Space Age. Known as the "Moonwatchers," these largely forgotten citizen-scientists helped professional astronomers by providing critical and otherwise unavailable information about the first satellites. In Keep Watching the Skies!, Patrick McCray tells the story of this network of pioneers who, fueled by civic pride and exhilarated by space exploration, took part in the twentieth century's biggest scientific endeavor." "Drawing on previously unexamined letters, photographs, scrapbooks, and interviews, Keep Watching the Skies! recreates a pivotal event from a perspective never before examined - that of ordinary people who leaped at a chance to take part in the excitement of space exploration."--Jacket